A dairy-based, protein-rich breakfast enhances satiety and cognitive concentration before lunch in overweight to obese young females: A randomized controlled crossover study - L.B. Dalgaard; D.Z. Kruse; K. Norup; B.V. Andersen; M. Hansen (Journal of Dairy Science, 2024)
ABSTRACT: The purpose of this study was to investigate if consumption of a high-protein, low-carbohydrate breakfast (PRO) leads to a lower subsequent ad libitum energy intake at lunch and the rest of the day compared with ingestion of an isocaloric low-protein, high-carbohydrate breakfast (CHO) or no breakfast (CON). The study was designed as a randomized controlled 3-period crossover study. Thirty young (18–30 yr) females with overweight to obesity (body mass index >25 kg/m2) in random order completed 3 separate experimental days where they consumed either a PRO, CHO, or CON breakfast test meal followed by an ad libitum lunch meal 3 h after breakfast. Participants were allocated to a sequence group by their inclusion number. The PRO and CHO breakfasts were matched in dietary fiber and fat content. Energy intake at lunch was calculated and dietary records were obtained for the rest of the day to calculate the total daily energy intake and macronutrient intake. Ratings of appetite sensations between meals and palatability of the test meals were assessed using visual analog scale sheets in intervals ranging from 10 to 30 min. In addition, blood samples were obtained at multiple time points separated by 10 to 60 min intervals between breakfast and lunch and were analyzed for appetite-regulating gut hormones, insulin, and glucose. Finally, performance in a cognitive concentration test was tested 150 min after breakfast. Compared with CHO and CON, the area under the curves for satiety, fullness, and satisfaction in the 3 h after breakfast were significantly higher after PRO, whereas the areas under the curve for hunger, desire to eat, and prospective eating were significantly lower after PRO. The appetite-regulating gut hormones cholecystokinin, glucagon-like peptide-1, and ghrelin in the hours after breakfast, energy intake during the ad libitum lunch meal, and the total daily energy intake did not differ significantly between PRO, CHO, and CON. However, the cognitive concentration test score was 3.5 percentage points higher for PRO, but not CHO, versus CON. A dairy-based high-protein, low-carbohydrate breakfast increased satiety sensation in the hours after breakfast but did not reduce total daily energy intake compared with an isocaloric low-protein, high-carbohydrate breakfast or omitting breakfast. However, performance in a cognitive concentration test before lunch was enhanced after the high-protein, low-carbohydrate breakfast, but not the low-protein, high-carbohydrate breakfast, compared with omitting breakfast.